The physical parameters of the rocks of the sedimentary cover of the northwestern part of the DnieperDonetsk trough - M.I. Orlyuk; V.V. Drukarenko (Геофизический журнал, 2013)
Density and volume magnetic susceptibility of rocks from 8 boreholes drilled in northwestern part of the DnieperDonets Depression were studied as well as variations of these values for the major rock types found in each of the wells. In accordance with the data the density of rocks of the same type is changed widely for both separate wells and sedimentary cover section as a whole. Decompacted rocks spaces accompanied by increased values of magnetic susceptibility are revealed. Such spaces may be potentially oilandgas bearing.